Uterus globulin associated protein 1 (UGRP1) is a potential marker of progression of Graves' disease into hypothyroidism. (20th August 2019) - Zhou, Zheng; Zuo, Chun-Lin; Li, Xue-Song; Ye, Xiao-Ping; Zhang, Qian-Yue; Wang, Ping; Zhang, Rong-Xin; Chen, Gang; Yang, Jia-Lin; Chen, Yue; Ma, Qin-Yun; Song, Huai-Dong
Abstract: Approximately 20% of Graves' disease (GD) patients may result eventually in hypothyroidism in their natural course. Uterus globulin-associated protein 1 (UGRP1) was associated with GD in our previous study. Here we investigated the role of UGRP1 in the development of autoimmune thyroid disease (AITD). The results showed that UGRP1 was expressed in the thyrocytes of most Hashimoto's thyroiditis (HT) patients and a proportion of GD patients (293 HT and 198 GD). The pathologic features of UGRP1-positive thyrocytes resembled "Hürthle cells", and were surrounded by infiltrated leukocytes. The positivity rate of TPOAb in UGRP1-positive GD patients was much higher than that in -negative GD patients. Moreover, UGRP1 was co-expressed with Fas and HLA-DR in the thyrocytes of AITD patients. We also found IL-1β but not Th1 or Th2 cytokines was able to upregulate the expression of UGRP1. Our findings indicated that UGRP1 may be a novel marker in thyrocytes to predict GD patients who develop hypothyroidism. Highlights: UGRP1 was highly expressed in the thyroid tissues from most HT patients and a proportion of GD patients. Clinical and pathological features of UGRP1-positive GD patients resembled HT patients. UGRP1 was co-expressed in the thyrocytes with Fas and HLA-DR. IL-1β was able to upregulate the expression of UGRP1 in thyrocytes. UGRP1-positive GD may be a new subtype of GD that tends to develop into hypothyroidism.